Pengembangan Sumber Daya Manusia Progam Tahfidz Al-Qur'an dalam Peningkatan Daya Saing Madrasah - Sunardi Sunardi; M. Labiq Mujtaba (At Tadbir: Islamic Education Management Journal, 2025)
This research aims to analyze the Human Resource Development (HRD) management of the Al-Qur'an tahfidz program and its role in enhancing the madrasa's competitiveness at MTs Madrasatul Qur'an Tebuireng Jombang. The demand for competitiveness in the modern era requires madrasas to possess unique advantages; however, tahfidz programs are often not supported by strategic human resource management for their teachers. This study employed a qualitative approach using a case study method. Data were collected through in-depth interviews with madrasa leadership and tahfidz coordinators, participatory observation, and documentation analysis of program planning and evaluation. The results indicate that HRD management is executed in two main structured stages: (1) Strategic planning, which includes annual coordination meetings for needs analysis, selective recruitment based on high qualification standards (proficient 30-juz memorization and pedagogical skills), and proper teacher placement. (2) Comprehensive implementation, which integrates professional development (methodology training), managerial development (supervision and evaluation), and spiritual guidance (halaqah and religious studies). A key finding reveals that this model is reinforced by close coordination between the madrasa and the dormitory (asrama). It is concluded that the synergy between selective strategic planning and integrated (professional-spiritual) comprehensive implementation effectively forms superior and high-character tahfidz teacher human resources, which serves as a key factor in enhancing the madrasa's institutional competitiveness.